Enabling highly reversible sodium metal cycling across a wide temperature range with dual-salt electrolytes. Issue 17 (26th April 2021) - Thenuwara, Akila C.; Shetty, Pralav P.; Kondekar, Neha; Wang, Chuanlong; Li, Weiyang; McDowell, Matthew T.
Abstract : A new dual-salt liquid electrolyte is developed that enables the reversible operation of high-energy sodium-metal-based batteries over a wide range of temperatures down to −50 °C. Abstract : New rechargeable battery chemistries that can operate at lower temperatures than Li-ion batteries are necessary for emerging applications such as electric flight. Sodium metal anodes have shown high coulombic efficiency and encouraging cycling behavior for high-energy batteries at room temperature, but electrochemical behavior of sodium at low temperatures has rarely been explored. Here, we show that sodium metal anodes can be cycled with high coulombic efficiency down to −50 °C when using diglyme-based electrolytes with dual salts, which surpasses the low-temperature performance of graphite anodes in Li-ion batteries. This novel electrolyte shows low overpotential and an average coulombic efficiency of 99.0% over 50 cycles when tested at −40 °C, as well as promising performance over a range of higher temperatures. The high coulombic efficiency of sodium cycling at low temperatures is attributed to the formation of a uniform SEI that is rich in inorganic species, as revealed by cryogenic transmission electron microscopy and X-ray photoelectron spectroscopy. These results are superior to lithium metal, which has exhibited relatively low coulombic efficiency at low temperatures in a variety of electrolytes. Our findings thus demonstrate the particular promise of sodium-metal-based batteries for use in cold environments.